Teachers and Students’ Perceptions towards Using ICT in ELT in Model Schools - Saud, Dammar Singh (Journal of Tikapur Multiple Campus, 2023)
In this digital age, new technologies help us overcome geographical and cost barriers in teaching and learning. This study employs a mixed-methods research design to explore the perspectives of English Language Teaching (ELT) teachers and students towards the use of Information and Communication Technology (ICT) in English language classrooms in two model secondary schools located in the Darchula district. The sample comprised four teachers and 60 students, who were selected through purposive selection and simple random sampling respectively. The study utilized a set of questionnaires for the students and a semi-structured interview for the teachers to collect data. The thematic analysis was used to analyze the collected data to derive insights into the teachers’ and students’ perceptions and experiences of using digital technologies in English language classrooms. The findings suggest that while the participants have positive attitudes towards integrating ICT in English language classrooms, they also face significant challenges, such as a lack of adequate training and technical support, which hinder the effective use of digital technologies in teaching and learning. The study underscores the need for policymakers and educational institutions to provide adequate resources and support to facilitate the effective integration of ICT in English language teaching.